Identifikasi lokasi rawan kecelakaan untuk peningkatan keselamatan jalan (studi kasus Jalan Tambak-Cibugang KM 71-81, Kabupaten Serang, Banten) - Abdul Anwar Cahyo Wicaksono; M. Oka Mahendra; Hadi Wiguno (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2026)
Road safety is an essential aspect of transportation infrastructure planning and management, especially considering the high rate of traffic accidents in Indonesia. The Tambak–Cibugang Road, KM 71–81, located in Serang Regency, Banten, is a strategic route that has shown a high accident rate in recent years. This study aims to identify accident-prone areas, analyze their causal factors, and provide technical recommendations to improve driver safety. The method employed is a descriptive-quantitative approach, involving primary and secondary data collection, calculation of the Equivalent Accident Number (EAN), blackspot identification using the Blackspot Identification (BKA) method, and prioritization of locations through the Upper Control Limit (UCL). Accident data were obtained from relevant agencies for the period 2020–2024, covering the number of incidents, fatalities, serious injuries, minor injuries, and material losses. The analysis results indicate that KM 78 and 81 are identified as locations, with values of 462 and 435, respectively, as these exceed the BKA value of 325. Contributing factors to accidents include poor road geometry, limited traffic signs, insufficient road lighting, and pavement damage such as cracks, potholes, and uneven surfaces. Technical recommendations for improvements include road geometry adjustments, additional traffic signage, enhanced road lighting, and pavement rehabilitation. The implementation of these recommendations is expected to significantly reduce accident rates and improve safety for road users.